Optimization of a logistics network considering allocation of facilities and taxation aspects - Furlanetto, Bruno Vinícius Ribeiro [UNESP]; Marins, Fernando Augusto Silva [UNESP]; da Silva, Aneirson Francisco [UNESP]; Defalque, Cristiane Maria [UNESP] (FapUNIFESP (SciELO), 2021)
This article analyzes the impacts of operational and tax changes in a logistics network, considering the location of facilities and the following taxes: the Brazilian State Excise Tax on Circulation of Goods and Services, the Import Duty, the Brazilian State Excise Tax in Tax Substitution, the Social Integration Program, the Contribution for the Financing of Social Security and the Brazilian Federal Excise Tax on Industrialized Products. The influence of incorporations and outsourcing of distribution services in solving global localization issues concerning various links in a chain suplly has also been considered. The problem was modeled and solved by the GAMS modeling language using Solver CPLEX. The proposed Mixed Integer Linear Programming model minimizes operating costs taking into account tax benefits and the best use of the credits related to the Tax on Circulation of Goods and Services of a multiproduct network. A real application involving a company in the animal feed production sector was developed. The results showed that the model allowed to evaluate conveniently how the choice of the facilities and the characteristics of the product flows impacted the overall costs of the system. The results also evidenced the need to make decisions based on the existing tax structure, since the scenarios without tax optimization generated substantial losses to the companies. This information added quality to the manager of the company studied.
Otimização de uma rede logística considerando alocação de instalações e aspectos tributários
Keywords: Animal feed industry; Brazilian taxes; Localization of facilities; Logistics networks; Mixed integer linear programming; Optimization